Research on characteristics of heavy metals (As, Cd, Zn) in coal from Southwest China and prevention method by using modified calcium-based materials. (15th December 2016) - Li, Shan; Guo, Shengli; Huang, Xiao; Huang, Tao; Bibi, Irshad; Muhammad, Faheem; Xu, Guojing; Zhao, Ziqiang; Yu, Lin; Yan, Yujie; Jiao, Binquan; Niazi, Nabeel Khan; et al.
Highlights: Content, characteristics, transformation of heavy metals in coal and ash are discussed before and after combustion. Modified calcium carbonate (CaCO3 ) is used as an additive to treat heavy metals. The migration and release of heavy metals in coal is studied and tested in the experiments. Abstract: Coal plays an important role in the Chinese energy source. The heavy metals released from combustion process stay in the environment and are not easily degraded. This paper examines 8 coal samples from China. It explores the content, characteristics, transformation and control of heavy metals through the microwave digestion, sequential chemical extraction, static burning test and X-ray diffraction (XRD) methods. The zinc (Zn) and cadmium (Cd) in coal mainly exist in exchangeable, sulfide, and residual forms. The arsenic (As) content is mainly present in the sulfide binding state. For these three elements, degrees of organic speciation are not considered to be important and the residue speciation mainly occurs in coal ash. After coal combustion, the heavy metals in coal ash are relatively enriched, and the harm to the environment cannot be ignored. Most of the Cd, As and Zn residues are released into the atmosphere and their volatility rates can be ordered as follows: As > Zn > Cd. There are significant differences in mineral composition between the main phases and mineral carriers of heavy metals in coal and ash. Based on these differences, modified calcium carbonate (CaCO3 ) is used as an additive. In orthogonal experiment, the optimal parameters for treating heavy metals are the temperature (1000 °C), metal salt (Al2 (SO4 )3 ), and ion ratio (γ = 15). Under this condition, the volatilization rates of heavy metals (As, Cd and Zn) decreased remarkably.